2017
DOI: 10.1016/j.vaccine.2017.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor diode laser device adjuvanting intradermal vaccine

Abstract: A brief exposure of skin to a low-power, non-tissue damaging laser light has been demonstrated to augment immune responses to intradermal vaccination. Both preclinical and clinical studies show that this approach is simple, effective, safe and well tolerated compared to standard chemical or biological adjuvants. Until now, these laser exposures have been performed using a diode-pumped solid-state laser (DPSSL) devices, which are expensive and require labor-intensive maintenance and special training. Developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 23 publications
4
33
0
Order By: Relevance
“…In contrast, the NIR laser adjuvant did not induce an IgE response to intradermal vaccination. Our previous study showed that the NIR laser adjuvant induces selective cellular signaling without inducing apparent tissue inflammation (4, 25). The current study further demonstrates that the NIR laser adjuvant is able to selectively modulate the most versatile and important cell population to augment adaptive immune responses, namely migDC, without inducing adverse IgE responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the NIR laser adjuvant did not induce an IgE response to intradermal vaccination. Our previous study showed that the NIR laser adjuvant induces selective cellular signaling without inducing apparent tissue inflammation (4, 25). The current study further demonstrates that the NIR laser adjuvant is able to selectively modulate the most versatile and important cell population to augment adaptive immune responses, namely migDC, without inducing adverse IgE responses.…”
Section: Discussionmentioning
confidence: 99%
“…The local inflammatory milieu created by the death of keratinocytes during skin laser microporation was similarly responsible for activation of XCR1 + DCs, thereby inducing tumor antigen-specific CD8 + and CD4 + T cell responses. We and others demonstrated that application of non-tissue damaging lasers in skin also induces an immunostimulatory microenvironment that activates DCs (6, 25). The application of a pulsed wave (PW) 532 nm laser increases the motility of APCs in skin and increases antigen-positive CD11c + DCs in the skin-draining lymph node (dLN) (26), augmenting an anti-influenza T H 1-skewed immunity, resulting in suboptimal protection (4).…”
Section: Introductionmentioning
confidence: 98%
“…This immunostimulatory milieu with the laser adjuvant led to a mixed T H 1‐T H 2 immune response to the whole inactivated influenza vaccination. Kimizuka et al expanded this finding showing that economical semiconductor laser diodes have adjuvant effect . A Gallium arsenide (GaAs) diode laser emitting 1061 nm (Axcel Photonics, Marlborough, MA) at an average irradiances of 5 W/cm 2 or Indium phosphide (InP) diode lasers emitting 1258 (Innolume, Dortmund, Germany) or 1301 nm (SemiNex Co., Peabody, MA) at an average irradiances of 1‐2 W/cm 2 over 1 minute replicated the adjuvant effect of the large diode‐pumped solid‐state Nd:YVO 4 laser system on the intradermal influenza vaccine without inducing damage or inflammation in the exposed tissue.…”
Section: Ultrashort Pulsed Laser Adjuvantmentioning
confidence: 56%
“…Kimizuka et al expanded this finding showing that economical semiconductor laser diodes have adjuvant effect. 42 A Gallium arsenide (GaAs) diode laser emitting 1061 nm (Axcel Photonics, Marlborough, MA) at an average irradiances of 5 W/cm 2 or Indium phosphide (InP) diode lasers emitting 1258 (Innolume, Dortmund, Germany) or 1301 nm (SemiNex Co., Peabody, MA) at an average irradiances of 1-2 W/cm 2 over 1 minute replicated the adjuvant effect of the large diode-pumped solid-state Nd:YVO 4 laser system on the intradermal influenza vaccine without inducing damage or inflammation in the exposed tissue. These low-cost handheld laser devices are 10-100 times less expensive than high-frequency, ultrashort pulsed lasers, which establish the feasibility of the laser adjuvant approach for use in the clinic.…”
Section: Non-pulsed Laser Adjuvantmentioning
confidence: 99%
“…The skin is rich in immune cells, including antigen-presenting cells (APCs) such as keratinocytes (KCs), macrophages (M⌽), and dendritic cells (DCs), as well as CD4 ϩ T cells and CD8 ϩ T cells, which are strategically positioned in the epidermis and dermis to be stimulated with various type of adjuvants (6). Skin exposure to various types of lasers has been successfully used to remove skin fine lines and wrinkles, and hence lasers represent excellent chemical-and biological-free adjuvants to enhance immune responses to vaccines (7)(8)(9)(10)(11)(12)(13)(14)(15). There are four different types of laser devices: (i) ultrashort pulsed lasers, (ii) nonpulsed lasers, (iii) nonablative fractional lasers, and (iv) ablative fractional lasers (13).…”
mentioning
confidence: 99%